Hubungan Pemberian Opini Audit oleh Auditor dan Laba Usaha Terhadap Return Saham di Bursa Efek Indonesia - Handayani, Revita Dwi (Keizai, 2025)
This study was conducted to see the effect of the relationship between the provision of audit opinions on companies and operating profit on stock returns of companies listed on the Indonesia Stock Exchange in 2021. The basis of this study is to test the consistency of the provision of audit opinions and operating profit on stock returns by looking at the relationship between signal theory. The type of research data is cross-section with a sample of 430 companies. The results of the study explain that as many as 342 companies obtained an unqualified opinion with the results that there is a positive relationship between the provision of opinions on stock returns. Then as many as 84 companies that obtained an unqualified opinion with an explanatory paragraph gave a negative relationship to stock returns. Then as many as 3 companies that obtained a qualified opinion and 1 company that obtained an adverse opinion had no relationship to stock returns. Finally, there is a positive relationship between operating profit and stock returns.